Multi-filament gas inflows fuelling young star-forming galaxies - Martin, D. Christopher; Ceverino, Daniel (Nature astronomy, 2019)
Theory suggests that there are two primary modes of accretion through which dark-matter halos acquire the gas to form and fuel galaxies: hot- and cold-flow accretion. In cold-flow accretion, gas streams along cosmic web filaments to the centre of the halo, allowing for the efficient delivery of star-forming fuel. Recently, two quasar-illuminated H i Lyman ɑ (Lyα)-emitting objects were reported to have properties of cold, rotating structures1,2. However, the spatial and spectral resolution available was insufficient to constrain the radial flows associated with connecting filaments. With the Keck Cosmic Web Imager (KCWI)3, we now have eight times the spatial resolution, permitting the detection of these inspiralling flows. To detect these inflows, we introduce a suite of models that incorporate zonal radial flows, demonstrate their performance on a numerical simulation that exhibits cold-flow accretion, and show that they are an excellent match to KCWI velocity maps of two Lyα emitters observed around high-redshift quasars. These multi-filament inflow models kinematically isolate zones of radial inflow that correspond to extended filamentary emission. The derived gas flux and inflow path is sufficient to fuel the inferred central galaxy star-formation rate and angular momentum. Thus, our kinematic emission maps provide strong evidence that the inflow of gas from the cosmic web is building galaxies at the peak of star formation.